REGULATIONS OF MEMORY DEVELOPMENT IN PRIMARY SCHOOL STUDENTS - Khushbok JUMAYEV (Scholar Express Journal, 2023)
The article talks about memory, mnemonic ability, reproductive thinking, young schoolchildren, school, talent, perception, remembering and reflecting feelings, thoughts, speech, actions
Keywords: skills and competence; knowledge; voluntary and involuntary memorization